Diagnostics of Corrosion on a Real Bridge Structure. (7th September 2016) - Koteš, Peter; Brodňan, Miroslav; Bahleda, František
Abstract : Real bridge structures are affected by environmental conditions. The environmental loads in time cause the degradation of concrete and reinforcement. The diagnostics of real state of existing bridges are very important due to actual degradation and corrosion. In the frame of research activities of Department of Structures and Bridges, Civil Engineering Faculty, University of Žilina, the real bridge structure was observed for a few years. It is girder reinforced concrete bridge near town of Žilina in Slovakia. The results of diagnostics which focused on reinforcement corrosion are presented. The paper deals with reinforcement corrosion and its influence on the moment resistance of the existing concrete structures.